In Silico Analysis Applied to the Study of Cytotoxicity in Natural Products - Pamela Isabel Japura Huanca; Bianca Araújo Fernandes Veras; Igor de Sousa Oliveira; Sávio Benvindo Ferreira (Chemistry Proceedings, 2022)
With the emergence of technological advances, computational analysis in research has become promising by enabling the emergence of scientific production without the need for an experimental laboratory, and it has therefore begun to be used in various sectors, including cytotoxicity. From this perspective, the main objective of this study is to understand the importance of computational analysis for the study of cytotoxicity in natural products in addition to understanding scientific advances on this topic. Thus, this is a narrative-type bibliographic review, carried out between March and September 2022, through the digital databases of Pubmed, SciELO, and the Virtual Health Library with the adoption of the search formula configured with the available descriptors: “in silico analysis”, “cytotoxic”, and “natural products”. This work reaffirmed the importance of computer simulations on cytotoxicity in natural products and provided verification that these types of analyses are a source of knowledge about the structures of natural products, emphasizing the use of in silico analysis of cytotoxic agents, anticancer action, and the treatment of other pathologies. With regard to effectiveness, it is clear that the software reflects results that are similar to studies carried out in vivo. It is noteworthy that the in silico method has an accentuated scientific importance as it allows for a greater adaptability and a lower cost of time and space for research. Thus, such methodology becomes essential in the process of cytotoxicity analysis, obtaining great potential in pharmacological research.